(untitled) (Journal of Educational Sciences, 2020)
The article describes the effectiveness of complex use of modern technical means in teaching biology. Currently, the system of higher education in Kazakhstan is undergoing a new stage of modernization. Curricula and training programs for young professionals are updated. In turn, there are high requirements to the level of professional and pedagogical training of teachers. In this regard, recently the interest of students, undergraduates, teachers, departments of faculties, universities to innovative technologies of education and education of specialists is increasing. Through the use of information technology in the learning process, we understand the integrity of the world and contribute to the growth of general intelligence. In our opinion, the use of modern information technologies in the process of training future teachers in higher education institutions entails the emergence of new subjects, as well as the relevance of considering new forms and methods of teaching. As a result of the research, a new innovative content of biological education and upbringing, structural and content model, pedagogical conditions, didactic principles are provided. Experience-pedagogical work was carried out. The study of biology shows the effectiveness of teaching methods of modern technical means, such as video, media, audio and innovative teaching methods. Key words: innovations, innovative technologies, multimedia, case, role-playing game, Kahoot, Indoor Labs, interactive lectures.